Factors related to resting energy expenditure and physical activity of 6–9-year old children in two primary schools in the City of Tshwane metropolitan area - Wenhold, Friedeburg Anna Maria (University of Pretoria, 2021)
Thesis (PhD (Dietetics))--University of Pretoria, 2020.